The Existence of Tonasa Cement Factory and its Impact to Surrounding People in South Sulawesi, Indonesia - Kamaruddin, Syamsu A (TAWARIKH, 2013)
ABSTRACT: This study used a qualitative approach in which data collected are analyzed based on the interpretation of the researchers to provide a comprehensive description and explanation about the phenomenon of environmental change in communities around the factory of PT Semen Tonasa. The process of industrialization to the peasant area caused peopleâs social life change. As an agrarian tradition that worked as a peasant (subsistence), their life was changed into un-peasant or un-subsistence by the development of cement factory. It was more complex when there was interaction with the people work in the factory. This condition made the social change actually happened. Research result shown that social change about social stratification was changed from ascribed status to achieved status that based on education, power, and wealth; there was also change of value and attitude from mechanic to organic solidarity; and, then, ecosystem changed from agricultural to industry. The positive impacts were namely opportunity work and income, good education, transportation, etc. The negative impacts were namely reclamation, employee, and waste.KEY WORDS: The process of industrialization, peasant community, Tonasa cement factory, social changes, and positive and negative impacts.About the Author: Dr. Syamsu A. Kamaruddin is a Senior Lecturer at the Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), Jalan Baruga Raya, Antang, Makassar, South Sulawesi, Indonesia. The author can be reached at: syamsukamaruddin@gmail.comHow to cite this article? Kamaruddin, Syamsu A. (2013). âThe Existence of Tonasa Cement Factory and its Impact to Surrounding People in South Sulawesi, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.187-204. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 8, 2013); Revised (March 11, 2013); and Published (April 28, 2013).